There's Always a Way : How to Develop a Positive Mindset and Succeed in Business and Life. - Little, Tony (John Wiley & Sons, 2010)
Increase your business fitness and break world sales records. You can do it! You can increase your sales power. You can become more persuasive and effective in your business and your personal life. Most of all, you can learn the secrets of transforming fear, failure, and adversity into victory. Many people today recognize a powerful correlation between physical health and business success. Tony Little is living proof of this connection. Having worked his way up from poverty and sickness to become, as Jay Leno called him, "America's personal trainer," he is also the most successful an.